Laparoscopic cholecystectomy in childhood: a review of twenty-four consecutive cases - Ozcakir, Esra; Sancar, Serpil; Kaya, Mete (The European Research Journal, 2017)
Background. The experience with laparoscopic cholecystectomy in children remains limited. Therefore, we aimed to present our experience with this procedure. Methods. Between April 2011 and June 2016, retrospectively, data points of children who underwent laparoscopic cholecystectomy reviewed included demographics properties, indication for cholecystectomy, surgical technique, operative time, complications, and length of hospital stay. Results. Twenty-four children (5 were males with ages ranging from 2 to 17 years, mean: 10.5 years) underwent laparoscopic cholecystectomy. The indication for surgery was associated to symptomatic gallstones in all patients. The surgery was performed under general anesthesia and classical 4-port approach was done in twenty-two patients, and 2-port approach in combination with 2 portless 2.3-mm percutaneous graspers was used in two patients. The operating time ranged between 45 and 90 minutes (mean: 60 minutes). Two patients ended by open surgery. No complications occurred. Hospital stays ranged from 1-3 days. Conclusion. Laparoscopic cholecystectomy is safe and effective in children, and shows the same advantages reported in adults series.